Nadarjeni učenci v Sloveniji, Italiji, Angliji in na Danskem - primerjava zakonodajnih in programskih izhodišč - Kukanja-Gabrijelčič, Mojca (Šolsko polje, 2013)
This paper presents strategic documents in the field of gifted and talented education in the Republic of Slovenia, UK-England, Denmark and Italy. The purpose of the comparative study was to determine the extent to which and in what way the curricular and legislative background of elementary school in Slovenian, English, Italian and Danish educational systems , is favourable to gifted and talented students in terms of promoting and developing their potentials. We have found that there are major terminological gaps in the definitions of concepts referring to giftedness and talent; the Slovenian educational system does not have a universal/standard curriculum (educational) model for work with gifted and talented students or its alternative variety; no relevant empirical data and research results on working with these students are at hand; there are shortcomings in the technical and professional recognition and further pedagogical-psychological treatment of gifted/ talented students - in the relevant strategic platforms which would cover all areas of scientific discovery and further pedagogical-psychological care for gifted and talented students. The research has shown that from the perspective of legal and programming guidelines; obligation of inclusion and care for gifted and talented students; learning differentiation and acceleration; alternative learning opportunities the English educational system is the one that is best adapted to gifted and talented students while the Italian one is the least. In its curricular and legislative bases the Slovenian educational system takes the areas of discovering and working with gifted students into account, yet on the implementation level some shortcomings in the realisation of their potential are revealed.
Keywords: giftedness; nadarjenost; nadarjeni učenci; talent; talentiranost; school legislation; school systems; šolski sistemi; comparative analysis; šolska zakonodaja; primerjalne analize